2022
DOI: 10.1155/2022/8725030
|View full text |Cite|
|
Sign up to set email alerts
|

Image Analysis Application of Motherwort Total Alkaloid Injection in the Treatment of Postabortion Hemorrhage

Abstract: In order to reduce the possibility of postabortion hemorrhage leading to maternal death, the author studied the image analysis of postpartum hemorrhage based on Leonurus total alkaloid injection, combining research results, in order to explore the curative effect of Leonurus injection in treating postpartum hemorrhage. After treatment, the time and volume of vaginal bleeding were significantly lower than those in the control group ( P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…alkaloid, leonurine) could significantly facilitate hemostatic outcomes by promoting uterine contraction and blocking the uterine spiral vessels ( Jian et al, 2005 ; Ojewole, 2005 ; Xiaoju, 2009 ; Huizhen et al, 2021 ). Moreover, motherwort injection works on the lower uterus without the receptor saturation effect, which reduces the risk of adverse events caused by the excessive use of uterotonic agents ( Wenjing, 2022 ). Therefore, the prophylactic use of motherwort injection with or without oxytocin has been widely applied in Chinese tertiary hospitals to prevent postpartum and postabortion hemorrhage since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…alkaloid, leonurine) could significantly facilitate hemostatic outcomes by promoting uterine contraction and blocking the uterine spiral vessels ( Jian et al, 2005 ; Ojewole, 2005 ; Xiaoju, 2009 ; Huizhen et al, 2021 ). Moreover, motherwort injection works on the lower uterus without the receptor saturation effect, which reduces the risk of adverse events caused by the excessive use of uterotonic agents ( Wenjing, 2022 ). Therefore, the prophylactic use of motherwort injection with or without oxytocin has been widely applied in Chinese tertiary hospitals to prevent postpartum and postabortion hemorrhage since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%